PROSES PEMBUATAN VERNIS DARI SERBUK DAMAR MENGGUNAKAN PELARUT BERBASIS MINYAK HIDROKARBON (The Process of Making Varnish from Damar Powder Using an Oil-Based Hydrocarbon Solvent) - Redha, Fauzi (Baristand Industri Banda Aceh, 2013)
Study of process technology of varnish production from Damar (resin)powder using an hydrocarbon oil-based solvent has been done. The purpose of thisresearch is to obtain a simple varnish manufacturing technology and increase theeconomic value of the damar resin which was available in Aceh province. Solvents used inthis study were the solvent mixture of gasoline and kerosene to the variation ratio of70%:30%, 50%:50%, 30%:70%. Comparison between the raw material resin and solventfor 1:1.5 (w/v), and addition of methanol (methanol 70%) as an additive with variation of0%, 20%, 30% and 40%. The results obtained by testing the viscosity, density and theapplication characteristic of varnish including gloss, daubing impression, and speeddrying. From testing the physical properties of viscosity indicated that varnishâs viscosityobtained above the standard range varnishâs viscosity is 6-7 cP. Varnish viscosity obtainedis in the range of 216-300 cP. For testing density, overall varnish resulting from anyvariation give a specific gravity ranging from 0.774 g/ml - 0.895 g/ml and wasapproaching the standard value of SNI 06-1009-1989. The most satisfactory varnish isproduced from B1 treatment (solvent composition: 50% gasoline: 50% kerosene, theaddition of methanol to 20% by volume) which gave the lowest viscosity values at 216, 85cP, density of 0.881 g/mL, with a good application characteristics